Harmonization of Import Duty in the Form of Security Measures for Textile Products - Maulana, Jay; Sarjana, I Made; Jayantiari, I Gusti Agung Mas Rwa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 2 (2023)DO - 10.24843/JMHU.2023.v12.i02.p02, 2023)
This article aims to determine the principles and regulations of international trade and to analyze the regulation for imposing security measures on imports of fabric products. The method used in this study is a normative juridical legal research type, with a statutory approach or statute approach to analyze legal issues. This research finds that the principle of International Trade adopted by the Indonesian state/Government is essentially aimed at protecting domestic products to maintain a healthy trade climate. International Trade is regulated by General Agreement on Tariffs and Trade, General Agreement on Trade in Services, The Agreement on Trade-Related Aspects of Intellectual Property Rights and Dispute Resolution of the World Trade Organization. Furthermore, in regards to the imposition of security measures on the import of fabric products in Indonesia, it is regulated in the Minister of Finance Regulations and its amendments. However, the Ministerial Regulation felt to be contradictory to the Minister of Trade’s Regulation. So, it is considered less effective because it will only burden local entrepreneurs/companies who need material products from abroad, on one hand the volume of imports has been limited and on the other hand there is an additional imposition of import duty as a result of security measures.